Lipid Transfer Protein allergy in the United Kingdom: Characterization and comparison with a matched Italian cohort. Issue 7 (14th March 2019) - Skypala, Isabel J.; Cecchi, Lorenzo; Shamji, Mohamed H.; Scala, Enrico; Till, Stephen
Abstract: Background: Although pollen‐related food allergy occurs in all European populations, lipid transfer protein (LTP) allergy is considered to manifest mainly in Mediterranean countries. We aimed to characterize adults presenting with LTP allergy in a northern European country. Method: The clinical history and sensitization patterns of subjects born and residing in the United Kingdom (UK), with a prior diagnosis of LTP allergy and sensitization to the peach LTP allergen Pru p 3, were compared to UK subjects with pollen food syndrome (PFS). The sensitization patterns were also evaluated against a matched cohort of Italian subjects diagnosed with LTP allergy. Results: None of the 15 UK PFS subjects had a positive SPT to LTP‐enriched peach reagent, compared to 91% of the 35 UK LTP subjects. The UK LTP cohort were also more likely to have positive skin prick tests to cabbage, lettuce and mustard and sensitization to the LTP allergens in peach, walnut, mugwort and plane tree These sensitization patterns to individual allergens were not significantly different to those obtained from the Italian LTP subjects, with significant correlations between Pru p 3 and the LTP allergens in peanuts, walnuts, plane tree and mugwort in both groups. Conclusion: Native UK subjects with LTP allergy are not dissimilar to those with LTP allergy in southern Europe. Testing to LTP‐enriched peach SPT reagent and/or LTP allergens in peach, walnut, mugwort and plane tree may enhance diagnostic accuracy. Abstract : UK‐born adults can develop Lipid Transfer Protein (LTP) allergy. Allergen sensitisation patterns in UK LTP allergic subjects are not significantly different to matched Italians with LTP allergy. Skin prick testing (SPT) with peach reagent is a useful diagnostic tool; the majority of UK LTP allergic subjects tested positive to peach, whereas none of those with Pollen Food Syndrome (PFS) did so.